Vasoactive Intestinal Peptide modulates trophoblast-derived cell line function and interaction with phagocytic cells through autocrine pathways - Vota, Daiana Marina (2016)
Trophoblast cells migrate and invade the decidual stroma in a tightly regulated process to maintain immune homeostasis at the maternal-placental interface during the first weeks of pregnancy. Locally synthesized factors modulate trophoblast cell function and their interaction with maternal leukocytes to promote the silent clearance of apoptotic cells. The vasoactive intestinal peptide (VIP) is a pleiotropic polypeptide with trophic and anti-inflammatory effects in murine pregnancy models. We explored the effect of VIP on two human first trimester trophoblast cell lines, particularly on their migration, invasiveness and interaction with phagocytic cells, and the signalling and regulatory pathways involved. We found that VIP enhanced trophoblast cell migration and invasion through the activation of high affinity VPAC receptors and PKA-CRE signalling pathways. VIP knocked-down trophoblast cells showed reduced migration in basal and leukemic inhibitor factor (LIF)-elicited conditions. In parallel, VIP-silenced trophoblast cells failed to induce the phagocytosis of apoptotic bodies and the expression of immunosuppressant markers by human monocytes. Our results suggest that VIP-mediated autocrine pathways regulate trophoblast cell function and contribute to immune homeostasis maintenance at placentation and may provide new clues for therapeutic intervention in pregnancies complicated by defective deep placentation.